Assessing full immunisation coverage using lot quality assurance sampling in urban and rural districts of southwest Nigeria (2013)
Background: This study was conducted to identify administrative wards (lots) with unacceptable levels of full child immunisation coverage, and to identify factors associated with achievement of a complete child immunisation schedule in Ibadan North East (IBNE) and Ido local government areas (LGAs) of Oyo State, Nigeria. Methods: A cross-sectional survey involving 1178 mothers, 588 from IBNE LGAs and 590 from Ido LGAs, with children 12–23 months of age was conducted. Children were considered ‘fully-immunised if they received all the vaccines included in the immunisation schedule. Lot quality assurance sampling was used to determine lots with acceptable and non-acceptable coverage. Samples were weighted based on the population by lot to estimate overall coverage in the two LGAs and a logistic regression model was used to identify factors associated with the fully immunised child. Results: Mean age of the mothers was 28.5+5.6 and 28.1+6.0 years in IBNE and Ido LGAs, respectively. Eleven of 12 wards in IBNE and all the wards in Ido had unacceptable coverage. The proportion of fully immunised children was 40.2% in IBNE and 41.3% in Ido. Maternal age ≥30 years, retention of an immunisation card, completion of tertiary education, or secondary education, hospital birth and first-order birth were significant predictors of complete childhood immunisation. Conclusion: The level of full immunisation coverage was unacceptable in almost all the wards. Educational inter vention on the importance of completion of immunisation schedule should target young, uneducated mothers, mothers who delivered their babies at home and those with a high birth order.